Nicander of Colophon's Theriaca : a literary commentary - Overduin, Floris, 1977- (Mnemosyne, Supplements, 2014)
In modern times the Theriaca of Nicander of Colophon (2nd century BCE) has not attracted many enthusiasts. Its complicated style, abstruse diction and technical subject matter - venomous bites and their remedies - have long put off classical scholars. In the wake of renewed interest in Hellenistic poetry, however, Nicander's dark poetry deserves new appreciation. In this book Floris Overduin provides a literary commentary on the Theriaca , focusing on Nicander's artistic merits. Viewed against the background of Alexandrian aesthetics and the didactic epic tradition, Nicander deserves pride of place among his Hellenistic peers. This book, the first full commentary in English, may thus contribute to the reappraisal of Nicander's Theriaca as a work of literature, not science.